Lesson Learned From the COVID-19 Protection Program for Health Care Workers in Nopparat Rajathanee Hospital. - Tosbovorn, Somboon; Chongchitpaisan, Wanna; Bandhukul, Adul; Jangsanam, Manuschanok (Journal of Preventive Medicine Association of Thailand, 2021)
The COVID-19 pandemic posted a risk of infection among health workers (HW). The effective protective measure for HW resulted in healthcare worker safety. The Nopparat Rajathanee hospital provided the occupational health exposure control measures to prevent HW exposure to the virus. From 13th January to 30th March 2020 the hospital took care of 50 COVID-19 patients. There were 805 HW under contact disease investigation, most of these were nurses and nurse aides (80%) and doctors (10.9%). The HW who were estimated high risk due to close contact with the patients were 2.7% and those quarantined were 2.0%. Health personal involved were 3 doctors, 5 nurses, 5 nurse aides and 3 other personal. There are no infected HW in the hospital.